Poetics and paradigm of post/Yugoslavian antiwar feminist and/or women’s novel: Interpretation of the phenomenon of alcoholism in Rio bar by Ivana Sajko (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
This paper is founded on the challenge of opening a new field of research for genre variations of novels with the topic of Yugoslav wars in which numerous regional women writers tried their hand. To analytically cover the heterogeneous and usually hardly accessible field it was required to create an innovative and functional theoretical-critical framework of the research in the first place. In the theoretical construction of the paper, there were identified and generated two coordinates or transnational post/Yugoslav approach and transnational feminism. The context of the primary dimension includes destabilizing and overcoming national and canonical limiting values, while on the other hand disturbing the traditional position of women writers. The post/Yugoslavian phenomenon means the re/creation of the cultural with the goal of researching different perspectives on descriptive motives of the wars, the articulation of the female subject in the text and against flexibility of the novel form. That way the traditional positions of the women writers get destroyed, that is, examine the processes of stereotyping of women writers and their work, criticizing double standards of evaluation presenting in a world of literature and, in the end, affirming the undeniable and crucial female role in the rise of the novel as a genre. Based on engaging feminist-ethical philosophical approach and interdisciplinary strategies of interpreting literary texts and literary phenomenons, the focus is on the active women writing or the articulation of an autonomous female subject in resistance or beyond the nation, as well as the neglected female experience of wars depicted in novels of contemporary women writers. The primary task of this paper is reflected in theorizing the subgenre of the novel from the examined aspect of poetic characteristics of the post/Yugoslavian antiwar novel. The difference the subject subgenre counts on is related to a female vision of repressive wars which figures with a foundation on the ethical critique of patriarchal and military structures. The umbrella term of post/Yugoslav as a transnational approach circles those discarded and unknown pieces of work by women writers within the framework of national literatures to introduce them into wider areas of the analysis and include them into the mosaic of the alternative antiwar stories of wars’ disintegration of Yugoslavia. Post/Yugoslav feminist and/or women’s novels represent literary reflections on the connecting feminine experience of living in traditional systems and culture with the main historical event of war’s disintegration of Yugoslavia. The types in which this subgenre occurs are feminist and/or women’s novels. Both types of novels affect the transformation from national to transnational literature in a way that disturbs the dominant representations of women and enters the framework of antiwar’s humanistic cognition of knowledge. The next step in the scientific description of this field represents variant of systematization of unexplored material, apropos creating a paradigmatic review of the genre or literary constellation that consists of eight thematic circles which are argued with a handful of examples. Although it is now spoken of eight different, but complementary thematic fields of the feminist and/or woman’s novel subgenre, the main emphasis is on the inclusiveness and communicativeness of the sketch in the direction of replenishment. The formed concentric circles for which the examples are given and which are scientifically described cover the big subgenre topics of the novel: a) wartime’s disintegration of the family, b) educational or novel of a girl growing up under the conditions of war, c) development of a female subject throughout the text, d) imprinting of war on the map of the female body e) disintegration of a female identity f) wartime forced exile g) the subject in the war space and h) destruction of the war’s and postwar’s or transitional’s community. Aiming to test uncovered scientific assumptions related to the post/Yugoslavian anti-war feminist and/or women’s novel, a hypothesis is put forward that follows the specific phenomenon of the representation of the conditioning of alcoholism in women and the experience of wars and transition, using the example of the novel Rio Bar (2006) by Ivana Sajko. The driving motive of Rio Bar is coded by the phenomenon of alcoholism, which has not been considered in existing research. Therefore, in this paper and when checking the scientific position of the field, the focus is on the literary shaping of the reworking of war and transitive trauma correlated with space, and the question of the articulation of the female subject from the position of revolt and not belonging to the order.
Keywords: post/Yugoslavian antiwar feminist and/or woman’s novel; transnational feminism; female subject; thematic circles; Ivana Sajko; Rio bar; alcoholism